2012
DOI: 10.1021/ja310952a
|View full text |Cite
|
Sign up to set email alerts
|

Base-Catalyzed Decarboxylation of Mandelylthiamin: Direct Formation of Bicarbonate as an Alternative to Formation of CO2

Abstract: The decarboxylation of mandelylthiamin is subject to general base catalysis (β = 0.26), an outcome that is inconsistent with the expected dissociative transition state in which CO(2) forms along with a residual carbanion. The results implicate a previously unrecognized associative route in which addition of water to a carboxylate followed by base-catalyzed proton transfer and C-C cleavage produces bicarbonate directly. Various reports of the presence or absence of base catalysis in decarboxylation reactions ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
25
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 29 publications
1
25
0
Order By: Relevance
“…Further examination showed that the decarboxylation of MTh is subject to general base catalysis. The catalytic reaction has a relatively low β value (0.26), indicating that there is a real but small degree of proton transfer in the same step as C-C cleavage [11]. There is no mechanism that we could cite to explain these conclusions in terms of production of CO 2 from MTh in a single step.…”
Section: Introductionmentioning
confidence: 96%
See 4 more Smart Citations
“…Further examination showed that the decarboxylation of MTh is subject to general base catalysis. The catalytic reaction has a relatively low β value (0.26), indicating that there is a real but small degree of proton transfer in the same step as C-C cleavage [11]. There is no mechanism that we could cite to explain these conclusions in terms of production of CO 2 from MTh in a single step.…”
Section: Introductionmentioning
confidence: 96%
“…Howe found that malonate monoanion is indeed a catalyst for the decarboxylation of MTh. However, when he tested the same reaction with acetic acid/acetate buffer, he saw acceleration as with malonate [11]. Further examination showed that the decarboxylation of MTh is subject to general base catalysis.…”
Section: Introductionmentioning
confidence: 98%
See 3 more Smart Citations